1982
DOI: 10.1111/j.1469-8137.1982.tb03236.x
|View full text |Cite
|
Sign up to set email alerts
|

NITROGEN METABOLISM IN POTERIUM SANGUISORBA DURING WATER STRESS

Abstract: SUMMARYWater stress, produced either by the addition of polyethylene glycol 4000 to water culture-grown Poterium sanguisorba or by withholding water from vermiculite-grown material, reduced nitrate reductase activity, but increased the level of glutamine synthetase in shoots, in roots the levels of all the nitrogen-assimilating enzymes studied were reduced. In both tissues these changes were accompanied by a fall in soluble protein and water content and by an increase in the total a-ammo and proline pools. Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(28 reference statements)
2
8
0
Order By: Relevance
“…The results presented here suggest that, as has been shown for other systems [24][25][26][27] GDH could play a role in ammonium assimilation during stress. The low water potential of the culture medium (~<-4.5bars) produces an osmotic stress in the explant.…”
Section: Resultssupporting
confidence: 61%
“…The results presented here suggest that, as has been shown for other systems [24][25][26][27] GDH could play a role in ammonium assimilation during stress. The low water potential of the culture medium (~<-4.5bars) produces an osmotic stress in the explant.…”
Section: Resultssupporting
confidence: 61%
“…Nitrogen metabolism has considerable importance during water stress in plants (Taylor et al, 1982). In the current study 8 amino acids increased, 8 decreased and 2 were unchanged by drought (Fig.…”
Section: Changes Of Soluble Amino Acids To Changing Water Statusmentioning
confidence: 86%
“…The reversal of chemical and morphological changes in roots due to desiccation is crucial to plant survival and crop productivity. It was previously reported (Taylor et al, 1982;Prasad et al, 1982) that a limited number of stress-related root metabolites reverted to control levels 3 d after desiccated plants were re-watered. Effects of rehydration on a broader array of root metabolites have not been examined in detail.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…During water stress nitrate reductase (NR) activity is lost more rapidly than most enzymes (Huffaker et al 1970). The other enzymes of the pathway of nitrate assimilation, nitrite reductase and glutamine synthetase (Taylor et al 1982), are relatively unaffected. Huffaker et al (1970) suggested that a rapid loss of NR activity could be part of a biochemical adaptation to water deficit; shutting off the nitrate assimilation pathway at the first step would reduce energy requirements during periods of stress and prevent accumulation of nitrite and ammonium.…”
mentioning
confidence: 99%